Music therapy and autism across the lifespan : a spectrum of approaches - Dunn, Henry (Music therapist); Mottram, Helen; Coombes, Elizabeth (Music therapist); Maclean, Emma (Music therapist); Nugent, Josie; Ockelford, Adam, 1959- (Jessica Kingsley Publishers, 2019)
The use of music therapy is long established with people with Autistic Spectrum Conditions. The combination of using music and relationship work in person-centred approaches supports the three main areas of difficulty people with autism often experience; social interaction, communication and imagination. Current research supports the positive psychological benefits of music therapy when people with autism spectrum conditions engage with music therapy. This book celebrates the richness of music therapy approaches and brings together the voices of practitioners in the UK. With a strong focus on practice-based evidence it showcases clinicians, researchers and educators working in a variety of settings across the lifespan.